Platypnoea orthodeoxia after hepatic surgery. (23rd April 2014) - Asrar ul Haq, Muhammad; Mutha, Vivek; Al-Kaisey, Ahmed; van Gaal, William J
Abstract : Platypnoea orthodeoxia is a rare clinical syndrome characterised by dyspnoea and deoxygenation exhibited in upright position with improvement in supine posture. Previously described aetiologies include cardiac (pericardial effusion or constrictive pericarditis), pulmonary (pneumonectomy, emphysema or amiodarone toxicity), abdominal (cirrhosis or ileus) or vascular (abdominal aortic aneurysm) causes. We report an unusual case of platypnoea orthodeoxia associated with patent foramen ovale and partial hepatic resection.